2014
DOI: 10.1002/2012rg000419
|View full text |Cite
|
Sign up to set email alerts
|

Internal gravity waves from atmospheric jets and fronts

Abstract: For several decades, jets and fronts have been known from observations to be significant sources of internal gravity waves in the atmosphere. Motivations to investigate these waves have included their impact on tropospheric convection, their contribution to local mixing and turbulence in the upper troposphere, their vertical propagation into the middle atmosphere, and the forcing of its global circulation. While many different studies have consistently highlighted jet exit regions as a favored locus for intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
321
0
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(352 citation statements)
references
References 366 publications
(595 reference statements)
10
321
0
9
Order By: Relevance
“…The summertime maxima in the subtropics occur because of the stronger activity of deep convective sources during summer. Gravity wave variances show great enhancement in the winter hemisphere over mid-and high latitudes where the polar night jet is strongest (Plougonven and Zhang, 2014), and due to strong mountain wave activity (Jiang et al, 2004a). The seasonal distribution of stratospheric gravity wave activity found in this study agrees well with other satellite climatologies based on limb measurements (e.g., Preusse et al, 2009a).…”
Section: Discussionsupporting
confidence: 87%
“…The summertime maxima in the subtropics occur because of the stronger activity of deep convective sources during summer. Gravity wave variances show great enhancement in the winter hemisphere over mid-and high latitudes where the polar night jet is strongest (Plougonven and Zhang, 2014), and due to strong mountain wave activity (Jiang et al, 2004a). The seasonal distribution of stratospheric gravity wave activity found in this study agrees well with other satellite climatologies based on limb measurements (e.g., Preusse et al, 2009a).…”
Section: Discussionsupporting
confidence: 87%
“…balanced or Rossby wave) and IGW components of circulation revealed that a small-size vortex formed at the inner edge of the polar vortex generating a divergent stratospheric flow (Figs. 5 and 6) directly above Northern Scandinavia acting as a gravity wave source in a similar way as the exit region of the tropospheric jets (Plougonven and Zhang, 2014). of inertia-gravity waves and confirm the observations of the radiosondes sounding.…”
Section: Discussion and Summarysupporting
confidence: 79%
“…gravity waves from the jet stream (Limpusavan et al, 2011). This source mechanism to generate internal gravity waves is known as spontaneous adjustment (e.g., Plougonven and Zhang, 2014). Sato (1999Sato ( , 2000 was among the first who suggested a similarity of the spontaneous adjustment at the tropospheric jet with that occurring in the stratosphere: Her numerical simulations using a gravity-wave resolving global circulation model revealed a "dominance of downward propagation of wave energy around the polar-night jet in the winter hemisphere, 5…”
Section: Introductionmentioning
confidence: 99%
“…Jet Instabilities. Processes related to jet imbalance and wind shear instability associated with the strong, rapidly evolving jet streams of intensifying cold fronts are well-known sources for gravity waves (32,44). Although typically weaker than their orographic cousins, the aggregate contribution of these gravity waves to the global distribution of energy and momentum flux may be comparable (45).…”
Section: Suomi Makes a Splash With Global Nightglow Imagerymentioning
confidence: 99%